Influence of Media on Process Stability in Sheet Metal Hydroforming - Geiger, Manfred; Merklein, Marion; Blankl, Andreas (International Journal of Materials & Product Technology, 2008)
The difference between sheet metal hydroforming and deep drawing is elementary: one half of the tool is substituted by hydraulic pressure. In order to guarantee an optimised forming result a tight cavity in the tool has to be created, since as soon as a leakage occurs, the forming pressure decreases rapidly and the forming operation is interrupted. The separation plane of the tool is the critical area for an occurring leakage because here a metallic sealing is often realised. Therefore, the objective of this paper is to present theoretical consideration on the leakage problematic in hydroforming. For illustration of the problem an existing process chain is presented in the beginning of this paper. Subsequently theoretical considerations are made. In the end a new strategy for defusing the leakage problem by changing the hydroforming media is presented in the outlook. Copyright © 2008 Inderscience Enterprises Ltd.
LFT Import::2019-07-29 (1505)
Keywords: Hydroforming; Process stability; Sheet metal